Colony stimulating factors (CSF) biosimilars. Progress? - Scotté, Florian; Launay-Vacher, Vincent; Rey, Jean-Baptiste (Targeted oncology, 2012)
Biosimilars are equivalent drugs for other biotechnological drugs for which patent has expired. These biopharmaceuticals are often looked upon as simple copies of parent drugs whose goal is solely to potentially generate costs savings. The expansion of available drugs is a subject of attention, criticism and quarrels, often related to a lack of product knowledge. These drugs are copies but need scientific development that must meet many strict rules. Many questions arise in connection with the marketing of several biosimilar drugs in the field of hematopoietic growth factors of white and red cells. Many of them should be discussed.